2012
DOI: 10.1902/jop.2012.110699
|View full text |Cite
|
Sign up to set email alerts
|

Presence of JP2 and Non‐JP2 Genotypes of Aggregatibacter actinomycetemcomitans and Attachment Loss in Adolescents in Ghana

Abstract: A. actinomycetemcomitans and AL were frequently found in Ghanaian adolescents. The school type was the strongest predictor of both presence of A. actinomycetemcomitans and AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 51 publications
1
87
1
Order By: Relevance
“…A total of 500 adolescents (mean age 13.2 years, SD: 1.5) were enrolled in the study undertaken in Ghana in 2009 (9). After 2 years, 397 (79.4%) were recruited for a periodontal re-examination (10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 500 adolescents (mean age 13.2 years, SD: 1.5) were enrolled in the study undertaken in Ghana in 2009 (9). After 2 years, 397 (79.4%) were recruited for a periodontal re-examination (10).…”
Section: Methodsmentioning
confidence: 99%
“…Twelve of the adolescents (seven girls and five boys) were recruited from one private school, and the remaining 86 were from five public schools. Detailed information on the study population, demographics, and ethics, including signed consents by parents has been reported on previously (9, 10). Knowledge on the socioeconomic status, the medical health status, and the intake of antibiotics within the past 3 months before the examination are available from the studies by Åberg and co-workers (9, 10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The JP2 genotype of A. actinomycetemcomitans is present in endemic form in populations of African origin (25)(26)(27) .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the high leukotoxicity of the JP2 genotype of Aggregatibacter actinomycetemcomitans has been associated with periodontal attachment loss in Afrodescendants (25)(26)(27) .…”
Section: Background and Justificationmentioning
confidence: 99%